Automation and Control of Vehicle Flow using Raspberry Pi - Leonardo Chancay-García; Walter Zambrano-Romero; Tatiana Zambrano-Solorzano (Informática y Sistemas, 2021)
The number of vehicles in the world's cities increases exponentially, this is the case of Latin American cities, and particularly in the city of Portoviejo, province of Manabí in Ecuador, has been growing considerably in recent years, the city has been expanding towards its surroundings. Due to this big number of vehicles, which also adds little planning to improve the use of public transport, little planning to improve urban vehicular flow, the centralization of administrative area and main shops in the city, are the main reasons why in certain times of the day the traffic can become a little slow.